ANALYSIS OF THE DYNAMICS OF ASSET RETURNS IN THE FINANCIAL MARKETS - Іванов, Ілля (Modern engineering and innovative technologies, 2024)
Effective investment portfolio management requires a deep and systematic understanding of the dynamics of different asset classes in financial markets. This study is dedicated to a comprehensive analysis of the historical profitability and risk of a wide